Running around (and such) - Byler, Linda (Byler, Linda. Lizzie searches for love, 2010)
A hot-tempered, high-spirited teenaged girl who hates housework, dislikes babies, and loves driving fast horses tries to fit in among the members of her Amish community. Based on the true experiences of the author's extended family.